Solar assisted cooling rule in indoor air quality - Ali M. Baniyounes; Yazeed Y. Ghadi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Indoor air quality as always is the centre of attention for researchers, architect developers and public health officials. As every-one know. The human exposure to a variety of indoor pollutants and the high cost of energy are the motivation for these kinds of studies. Fungus and mould growth has always been a problem in subtropical climate areas due to the high temperature and high humidity. Generally in institutional buildings, most of the internal heat load is generated by human body and thermal comfort is achieved with   extensive usage of recycled air and air conditioning. The main considerations in any air conditioning system economisers are based on the usage of recycled air and air ventilation. The current practice in an institutional building cooling system under subtropical climate is to curb the mould issue by overcooling large recirculation airflow to remove the moisture content from the air, which is considered as an expensive practice. The use of a solar desiccant cooling system to reduce moisture from the air and to improve indoor air quality is found to be economical, environmental friendly and readily achievable in the tropics. This technology is the future alternative to the conventional vapour compression cooling system to maintain human thermal comfort conditions and enhance indoor air quality. Solar desiccant cooling systems are also environmentally friendly and energy efficient. This paper presents review on a solar desiccant cooling system and its effect on indoor air quality. It first introduces the issue of air moisture, mould growth and indoor air quality and then the development and application of thermally activated desiccant cooling technologies.